(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Socialization was carried out in Sebayan Village, which aimed to increase the love for eating fish in an effort to overcome stunting. Fish consumption is still lacking in the community because of the lack of public knowledge regarding the nutrients contained in fish. This socialization activity took place in November 2023 in Sebayan Village. The approach used in this activity was door-to-door. The number of respondents who participated in this community service activity was 65, with 53 female and 12 male respondents. This form of socialization has been approved by village government organizations. The results of this study provide information on fish nutrition in the community. In addition, this activity can also be an effort to help reduce the incidence of stunting. This activity has previously been given a briefing and strengthening knowledge on the love of eating fish. Another aspect of this activity was that it was smooth.